Scattering of surface plasmon-polaritons in a graphene multilayer photonic crystal with inhomogeneous doping - Bludov, Yuliy V. (2016)
The propagation of a surface plasmon-polariton along a stack of doped graphene sheets is considered. This auxiliary problem is used to discuss: (i) the scattering of such a mode at an interface between the stack and the vacuum; (ii) the scattering at an interface where there is a sudden change of the electronic doping. The formalism is then extended to the barrier problem. In this system rich physics is found for the plasmonic mode, showing: total reﬂection, total transmission, Fabry-Perot oscillations, and coupling to photonic modes.